Verbal fluency tasks and attention problems in children with ADHD: evidence from fNIRS - Zouji Bian; Xiquan Ma; Yanhan Wang; Xiaodan Yu (Frontiers in Neurology)
BackgroundFunctional near-infrared spectroscopy (fNIRS) is a promising non-invasive neuroimaging tool for assessing cortical activity in children with attention-deficit hyperactivity disorder (ADHD). While Verbal Fluency Tasks (VFTs) are widely used in adolescents and adults, their application in younger children remains underexplored. This study aimed to examine cortical activation during a VFT in children with ADHD and its association with attention-related behavioral symptoms.MethodsThirteen children with ADHD (aged 7–9) and 13 matched neurotypically developed controls completed a VFT while undergoing fNIRS. Activation in the dorsolateral prefrontal cortex (DLPFC) was analyzed using mean amplitude, center of gravity (COG), and initial slope. Associations with the Swanson, Nolan, and Pelham Rating Scale (SNAP-IV) and Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition (DSM-V) scores were examined.ResultsChildren with ADHD showed significantly lower DLPFC activation and widespread negative patterns compared to neurotypically developed peers (p < 0.05). Mean activation amplitude was significantly correlated with inattention scores on both the SNAP-IV and DSM-V scales.DiscussionfNIRS revealed altered DLPFC activation in children with ADHD during VFT, underscoring its potential as an objective tool to support clinical assessment of attention deficits in younger populations.